(untitled) (BIRDEM Medical Journal, 2024)
Prader-Willi syndrome (PWS) is a rare multi-systemic genetic disorder with hyperphagic obesity. This complex syndrome is caused by lack of expression of paternally derived genes on chromosome 15q11-13. In classical PWS, major diagnostic features include neonatal hypotonia, feeding problem in infancy, rapid weight gain after infancy, hyperphagia, developmental delay, hypogonadotropic hypogonadism and characteristic facial features. With age, this disorder is further complicated with the development of scoliosis, juvenile diabetes and sleep apnea. Obesity is the most significant health problem for PWS patients. The cause of hyperphagia in PWS is unknown and likely multifactorial. Among the anorexigenic hormones, serum leptin concentration, which signals satiety to the hypothalamus, is found to be appropriately increased in proportion to higher fat mass in patients with PWS. Thus, unusually low plasma leptin levels or relative loss of sensitivity to leptin in PWS subjects could be an important factor in their obesity. We report a young girl with PWS with severe leptin deficiency, morbid obesity and type 2 diabetes mellitus. BIRDEM Med J 2024; 14(2): 103-107